2001
DOI: 10.1038/sj.ijo.0801571
|View full text |Cite
|
Sign up to set email alerts
|

Thinness and body shape of Playboy centerfolds from 1978 to 1998

Abstract: OBJECTIVE: Changes in the body weight and shape of Playboy centerfolds over the past two decades (1978 ± 1998) were examined. METHODS: The body mass index (BMI) and waist-to-hip circumference ratio (WHR) were obtained from measurements reported by 240 centerfolds (ages 19 ± 35 y). RESULTS: The 20-y averages (mean AE s.d.) were 18.1 AE 0.8 kgam 2 for BMI and 0.68 AE 0.03 for WHR, and there has been no appreciable change in either BMI or WHR in centerfolds over the past 20 y. Based on current recommendations fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 15 publications
2
38
0
9
Order By: Relevance
“…Whereas an increase in news coverage might have been expected to result in heightened awareness of overweight status, by emphasizing the increased prevalence of overweight, the stories may have contributed to the perception that overweight had become the norm. At the same time, the thin female body ideal portrayed in media imagery persisted across the two survey periods (20)(21)(22). Given that women's weight assessments became more forgiving during this time period, it would appear that media images do not dictate women's attitudes toward their weight or at least that they have become less influential in recent years.…”
Section: Resultsmentioning
confidence: 90%
“…Whereas an increase in news coverage might have been expected to result in heightened awareness of overweight status, by emphasizing the increased prevalence of overweight, the stories may have contributed to the perception that overweight had become the norm. At the same time, the thin female body ideal portrayed in media imagery persisted across the two survey periods (20)(21)(22). Given that women's weight assessments became more forgiving during this time period, it would appear that media images do not dictate women's attitudes toward their weight or at least that they have become less influential in recent years.…”
Section: Resultsmentioning
confidence: 90%
“…Studies have reported a significant change in the weight and size of female and male models portrayed throughout the media in western society and the concept of the 'perfect or ideal body' (8)(9)(10). Over time the cultural ideal for women's body size and shape has become considerably thinner and leaner and men's body size and shape has become stronger and more muscular.…”
Section: Types Of Media Exposurementioning
confidence: 99%
“…54 The blue curves in the Panels 1 and 2 of Figure 2 indicate the following: the ideals for white and black women, respectively, are 20.01 and 21.98-effectively, 20 and 22; the ideals for white and black men are 22.98 and 24.36. The white female ideal is close to, but somewhat higher than, the estimated mean value of BMI among Playboy centerfolds between 1978 and 1998, placed at 18.5 (standard error 0.8 units), based on the models' self-reported measurements (Katzmarzyk andDavis 2001, Sypeck et al 2006). Higher male ideals are consistent with, but somewhat lower than, the estimated mean BMI values of male models in Playgirl magazine, which ranged from 24.8 to 27.7 (also based on self-reports) over the period 1986-1997 (Spitzer, Henderson, and Zivian 1999).…”
Section: Evidence Of Differences In Sociocultural Ideals and Related mentioning
confidence: 99%